Management of post-surgical cervical pseudomeningocele causing spinal cord compression: a case report - Shehzad, Mishkat; Kaleem, Misbah; Saeed, Faizan; Bari, Ehsan (Journal of the Pakistan Medical Association, 2026)
Major neurological deficits secondary to compressive cervical pseudomeningocele are rarely encountered and only a limited number of cases have been documented in the literature. This report presents the case of a 64-year-old man who had progressive upper and lower limb weakness for the last six months. Magnetic Resonance Imaging (MRI) of the cervical spine showed stenosis from C3 to C6 level. Laminectomy of vertebral level C3-C6 with lateral mass fixation was done. On the third post-operative day, the patient developed quadriplegia along with swelling at the operative site. MRI revealed collection of Cerebrospinal Fluid (CSF) at the surgical site, compressing the cervical spinal cord. Evacuation of the accumulated fluid and bedside debridement was performed and a lumbar drain was placed, leading to interval neurological improvement. This case shows that bedside debridement and lumbar drain placement is a successful treatment option as an alternative to surgical management of symptomatic pseudomeningocele. Keywords: Compressive Pseudomeningocele; Laminectomy; Post-operative complication; Spinal cord compression.